Consumer Services аnd Entrepreneurial Initiatives оf the Population - E. A. Razomasova; A. T. Petrova; O. N. Vladimirova (Мир новой экономики)
Small businesses make a significant contribution to the social and economic performance of the country. Identification of unrealised entrepreneurial potential is an important task. Its implementation will not only allowing achievement of strategic goals, which were set by the President of the Russian Federation but also determined the further development of this sector of the economy. International comparisons have revealed a significant gap between Russia’s level of business development and that of the developed countries. In our country, the share of small and medium-sized businesses accounts for 20–25 per cent of GDP, while abroad, this figure reached a level of 60–75 per cent. It is possible to reduce the gap only by carrying out a quality policy in the field of promoting entrepreneurial initiatives, initiatives by the Federal authorities and public organisations. A policy of reduction of the level of administrative barriers with a simultaneous increase in financial capacity will allow existing and emerging entrepreneurs to act more proactively and openly, will launch business scaling mechanisms and increase the number of employees. In our study, we offer to existing and new entrepreneurs, and to authorities to pay close attention to the sphere of consumer services. This sphere provides ample opportunities for entrepreneurs to accumulate start-up capital for further investment in the economy. To determine the real interest of the population in entrepreneurship and consumer services, we conducted an online sociological survey of the population. The results of the survey allowed the establishment of the service market segments which are the most popular among potential entrepreneurs. Respondents mainly chose catering services, small repairs and home improvement, clearing. According to respondents, the prospect of business organisation in these sectors is associated with the development of urban space and the trend of urbanisation of the economy. It will allow these types of services to be in demand for a long time so they will be able to bring a stable income to the entrepreneur.